Tindakan Persetubuhan Mayat Ditinjau Dari Undang-Undang Nomor 1 Tahun 2023 Tentang KUHP - Sabina Salsabila; Rio Armanda Agustian; Toni; Adhika Adriansyah (BULLET : Jurnal Multidisiplin Ilmu, 2025)
This study wants to discuss the act of sexual intercourse with corpses when viewed from Law No. 1 of 2023 concerning the Criminal Code. The act of sexual intercourse on a corpse is often not considered in deciding a case by the judge. The perpetrator's actions are only acts that exist at the same time as sexual intercourse with a corpse. This study aims to find out and analyze the application of article 271 of Law No. 1 of 2023 concerning the Criminal Code to perpetrators of sexual intercourse on corpses from the theory of unlawful acts in criminal law and to find out and analyze interpretation methods related to acts of sexual intercourse against corpses reviewed from Law No. 1 of 2023 concerning the Criminal Code. The method in this study is normative juridical. The approach in this study uses a statue approach and a conceptual approach. The results of study show that the act of sexual intercourse with a corpse in the case discussed is a criminal act, especially included in the criminal act of treating a corpse uncivilly because it has fulfilled the elements as stated in article 271 of Law No. 1 of 2023 concerning the Criminal Code so that the perpetrator can be subject to a criminal penalty in the form of a maximum prison sentence of 2 years or a maximum fine of category III.